Reconstitution of the Ataxia-Telangiectasia Cellular Phenotype With Lentiviral Vectors - Carranza, Diana; Torres-Rusillo, Sara; Ceballos-Pérez, Gloria; Blanco-Jimenez, Eva; Muñoz-López, Martin; García-Pérez, José L.; Molina, Ignacio J. (Frontiers in Immunology, 2018)
Ataxia-telangiectasia (A-T) is a complex disease arising from mutations in the ATM gene (Ataxia-Telangiectasia Mutated), which plays crucial roles in repairing double-strand DNA breaks (DSBs). Heterogeneous immunodeficiency, extreme radiosensitivity, frequent appearance of tumors and neurological degeneration are hallmarks of the disease, which carries high morbidity and mortality because only palliative treatments are currently available. Gene therapy was effective in animal models of the disease, but the large size of the ATM cDNA required the use of HSV-1 or HSV/AAV hybrid amplicon vectors, whose characteristics make them unlikely tools for treating A-T patients. Due to recent advances in vector packaging, production and biosafety, we developed a lentiviral vector containing the ATM cDNA and tested whether or not it could rescue cellular defects of A-T human mutant fibroblasts. Although the cargo capacity of lentiviral vectors is an inherent limitation in their use, and despite the large size of the transgene, we successfully transduced around 20% of ATM-mutant cells. ATM expression and phosphorylation assays indicated that the neoprotein was functional in transduced cells, further reinforced by their restored capacity to phosphorylate direct ATM substrates such as p53 and their capability to repair radiation-induced DSBs. In addition, transduced cells also restored cellular radiosensitivity and cell cycle abnormalities. Our results demonstrate that lentiviral vectors can be used to rescue the intrinsic cellular defects of ATM-mutant cells, which represent, in spite of their limitations, a proof-of-concept for A-T gene therapy.